Effect of different types of exercise on sleep deprivation and functional capacity in middle aged patients after coronary artery bypass grafting - Atef, Hady; Helmy, Zeinab; Farghaly, Abeer (Sleep Science, 2020)
Introduction: There are still many gaps in research concerning the effect of different physical training modalities on sleep quality in the population underwent coronary artery bypass graft (CABG) surgeries.Objective: The purpose of this study was to compare the effect of different exercise types on sleep quality and functional capacity after CABG.Material and Methods: 80 Participants aged 45-65 years were randomized to two groups: aerobic group (AG), and combined aerobic and resistance group (ARG). Training lasted ten consecutive weeks with 30 uninterrupted sessions. The actigraph together with Pittsburg Sleep Quality Index (PSQI) were used in sleep quality assessment. Six-minute walk test (6MWT) was used in assessment of functional capacity. The actigraph (Actiwatch Minimitter Company, Incorporated (INC) - Sunriver, OR, USA) was placed on the non-dominant wrist and activities were monitored continuously while being recorded at one-minute intervals. The participants kept the device for a period of 96 hours, filled PSQI, and did 6MWT before the first and last training sessions.Results: There was significant decrease in the mean value of sleep latency, fragmentation index, light sleep duration and sleep quality scores (p<0.01); and significant increase in total sleep duration, deep sleep duration, number of points on the actigraphy, sleep efficiency and functional capacity in both (AG) and (ARG) (p<0.01), that difference was more significant in the aerobic group (AG) (p<0.01).Conclusions: Both modes of exercise (aerobic alone and combined aerobic and resistance exercises) can improve sleep quality and functional capacity, but isolated aerobic exercise can do that more significantly.
Keywords: Sleep Deprivation; Exercise; Coronary Artery Bypass; Actigraphy